THE IMPROVEMENT OF MSMEs' BUSINESS PERFORMANCE DURING THE COVID-19 PANDEMIC THROUGH FINANCIAL AND DIGITAL LITERACY - Athia, Ita; Soetjipto, Budi Eko; Efendi, Erfan (Fakultas Ekonomi dan Bisnis, UNTAN, 2023)
The pandemic has impacted the global economy, includingMSMEs,especially in financial issues such as minimal revenue flow and inadequate financial management. On the marketing side, there has been a decrease in demand due to the implementation of social restrictions, which will affect the company